THE BLACK BOX TESTING AND LOC METHOD APPROACH IN TESTING AND STREAMLINING THE PATIENT REGISTRATION PROGRAM - Joosten Joosten (Jurnal Riset Informatika, 2021)
Good software can be used if there is proper testing. The testing phase is quite important because the software needs to be tested before it is used by end users. In making software for animal hospitals there is no validation and verification so testing is needed. This study used information on the registration section of veterinary hospital patients and was tested by three Black Box Testing methods, namely Equivalence Class Partitioning (ECP), Boundary Value Analysis (BVA), and Decision Table plus the LOC approach. The test results of the three methods are that the percentage of invalid ECPs is greater than the valid ones, so the input value limit needs to be changed again. Then for BVA testing, the percentage of valid is higher than invalid. In the decision table, a shortening rule is made between operating services and other services so that it produces inpatient status and down payment automatically without choose it again and is tested again by the decision table by matching the estimation results of the two services.